Ballistic energy conversion: physical modeling and optical characterization. (December 2016) - Xie, Yanbo; Bos, Diederik; van der Meulen, Mark-Jan; Versluis, Michel; van den Berg, Albert; Eijkel, Jan C.T.
Abstract: The growing demand for renewable energy stimulates the exploration of new materials and methods for clean energy, a process which is boosted by nanoscience and emerging nanotechnologies. Recently a high efficiency and high power density energy conversion mechanism was demonstrated through the use of jetted charged microdroplets, which fully relies on the net charges stored in the electrical double layer within a hundred nanometers of the water/gas interface, and then delivered at a metal target for converting kinetic energy to electrical energy. The method is fundamentally different from the traditional electrokinetic conversion and electrostatic generators, termed as ballistic energy conversion. It has a great potential in further applications due to the ultra-simple device design and the use of water, avoiding the challenges of new materials inventions. However, thorough theory is still lacking for both a quantitative description and an optimization of this system. Here we model and experimentally characterize the physical properties of the ballistic energy conversion system. Our model predicts the optimal working conditions of the energy harvesting including initial velocity and jet size, as well as the key performance factors including efficiency, generated target voltage, and power density. The results show that by using maximally charged droplets, an appropriate size and initial velocity of microjet, the system efficiency can be over 90%, at a generated voltage below 1 kV and a power density of at least 100 W/m 2 . The combination of high efficiency, huge power density, simplicity and compactness makes the ballistic energy conversion generator a promising device for green energy conversion. Graphical abstract: We demonstrated the high efficiency energy conversion by decelerating high speed charged microdroplet, termed as "ballistic". However, the upper-limit of efficiency and the way to improve the system is still not known yet. We theoretically predict the ballistic conversion efficiency, power density and generated voltage supported by optical characterization. Highlights: Theories with optical characterization of ballistic energy conversion were built. Major performances are predicted - efficiency, power density and generated voltage. The direction of optimization of ballistic energy conversion was pointed out.